Fertility Responses of High-Skilled Native Women to Immigrant Inflows - Delia Furtado (Institute for the Study of Labor (IZA), 2014)
While there is debate regarding the magnitude of the impact, immigrant inflows are generally understood to depress wages and increase employment in immigrant-intensive sectors. In light of the over-representation of the foreign-born in the childcare industry, this paper examines whether college-educated native women respond to immigrant-induced lower cost and potentially more convenient childcare options with increased fertility. An analysis of U.S. Census data between 1980 and 2000 suggests that immigrant inflows are indeed associated with increased likelihoods of having a baby, and responses are strongest among women who are most likely to consider childcare costs when making fertility decisions namely, married women with a graduate degree. Given that women also respond to immigrant inflows by working long hours, the paper ends with an analysis of the types of women who have stronger fertility relative to labor supply responses to immigrant-induced changes in childcare options.
Keywords: D10; F22; J13; J22; R23; 330; immigration; fertility; child care; labor supply